Integration of GIS Technology and STEM in Geography Learning to Improve Students' Spatial Thinking Skills - Nurmuhniyanti M Hubaib; Bambang Syaeful Hadi (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2025)
The integration of Geographic Information System (GIS) technology and the STEM approach in geography education remains limited, particularly due to teachers’ insufficient technological proficiency. This study examines the partial and interactive effects of GIS based instruction and STEM-oriented learning on the spatial thinking skills of senior high school students. A quasi-experimental 2 × 2 factorial design was employed, involving 136 students drawn from intact geography classes, where individual randomization was not feasible. Spatial thinking skills were measured using a validated and reliable test instrument. Data were analyzed using descriptive statistics and two-way ANCOVA. The results indicated a significant main effect of GIS (η²p = 0.657, large effect), a moderate effect of STEM (η²p = 0.093), and a moderate-to-large interaction effect between GIS and STEM (η²p = 0.128). These results indicate that the combined implementation of GIS and STEM provides stronger support for the development of students’ spatial thinking skills than either approach applied independently. This study contributes conceptually by clarifying the role of GIS as a cognitive mediator within STEM-based geography learning, thereby extending existing research that has predominantly emphasized the technical application of GIS or the isolated effects of STEM instruction.